Chapter Introduction Imagining a World Without Heroes - Farrell, John (Taylor & Francis, 2023)
Utopian thinking has a typical opponent, the heroic-aristocratic culture which has its fullest expression in epic poetry. There is a perennial clash of values between the dignity of rank and personal achievement and rational utopian planning. Most of the major authors who have dealt with utopian themes find themselves caught in a dilemma between the inhumanity of heroic values and difficulty of imagining life without them.